Facile synthesis of mesoporous hierarchical ZnS@β-Ni(OH)2 microspheres for flexible solid state hybrid supercapacitors. Issue 103 (24th October 2016) - Wei, Chengzhen; Cheng, Cheng; Du, Weimin; Ren, Jiahui; Li, Man; Dong, Jianning; Liu, Kangfei
Abstract : Mesoporous hierarchical ZnS@β-Ni(OH)2 microspheres have been successfully synthesized via a facile route and exhibited good performance as electrode materials for supercapacitors. Abstract : Mesoporous hierarchical ZnS@β-Ni(OH)2 microspheres have been successfully synthesized via a facile route. In the synthesis process, ZnS spheres are used as the templates for the direct growth of β-Ni(OH)2 nanosheets on their surface. Owing to their unique structure and composition, when the mesoporous hierarchical ZnS@β-Ni(OH)2 microspheres were utilized as electrode materials for supercapacitors, which exhibited substantially enhanced specific capacitance (1361.7 F g −1 at 4.0 A g −1 ) compared with ZnS and β-Ni(OH)2 . Furthermore, a flexible solid state hybrid supercapacitor was assembled by using mesoporous hierarchical ZnS@β-Ni(OH)2 microspheres as a positive electrode and activated carbon as a negative electrode. The resulting flexible solid state device showed a specific capacitance of 170.97 mF cm −2 at 2.0 mA cm −2, and offered a volumetric energy density of 0.783 mW h cm −3 and a power density of 45.7 mW cm −3 . Impressively, the device displayed good mechanical flexibility under various bending angles from 0° to 180°. This study presents a novel and promising electrochemically active material for supercapacitors.